Addressing Underachievement Among Gifted High School Students in Mathematics: The Impact of the STAD Approach in Indonesia - Suryandari, Savitri; Hanurawan, Fattah; Chusniyah, Tutut; Hutagalung, Fonny Dameaty; Raman, Farah Izyan (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2025)
Enhancing educational outcomes for underachieving gifted students, defined as those with an IQ ≥ 110 but mathematics scores below 80%, requires innovative teaching strategies. This study investigates the effectiveness of the Student Teams Achievement Divisions (STAD) compared to conventional teaching for improving mathematics learning outcomes among underachieving gifted students. Using a experimental design with randomised pre-test and post-test groups, 60 students from class XII IPA at SMA Negeri 5 Surabaya were assigned to either the STAD (n=30) or control group (n=30). Data were analyzed using descriptive statistics and an independent t-test. The STAD group achieved a mean gain score of 39.633, compared to 27.267 for the control group, with a significant difference (t(58) = 7.380, p <0.001, d =1.91). These findings suggest STAD is effective for enhancing mathematics performance in this Indonesian population, supporting its use in collaborative learning contexts. Further research should explore long-term effects and additional outcomes.